Performance Analysis Of Liquid-Cooled Panel System For Air Conditioner Using Peltier Effect - Harun, Mohamad Haniff; Mohd Ab. Halim, Mohd Firdaus; Azahar, Arman Hadi; Yaakub, Muhamad Faizal; Md Basar, Mohd Farriz; Zainal Abidin, Amar Faiz; Mohd Aras, Mohd Shahrieel (Penerbit Akademia Baru, 2019)
This study reviews the recent advances of thermoelectric materials, modelling approaches, and applications. Thermoelectric cooling systems have advantages over conventional cooling devices, including compact in size, light in weight, high reliability, no mechanical moving parts, no working fluid, being powered by direct current, and easily switching between cooling and heating modes. In this study, it focused on the replacement of the outdoor unit (compressor) for conventional air-conditioner. This system using water as cooling agent in replacing refrigerant system. It involves using Peltier Effect which converts current to rise the temperature between the two junctions of the Peltier. The water will flow through these changes in temperature which results in cooling the air through the process. From this process, it taken 60 minutes in order to achieve 20.2 °C and consumed 1.3 A which is better rather using the conventional method. This can reduce the cost of the project in terms of maintenance, bills, materials and gases. This system can be operated without relying to the compressor which improve the systems in terms of noise, low electricity usage, small size and use water as coolant agent.